Evaluation of a focused library of N-aryl L-homoserine lactones reveals a new set of potent quorum sensing modulators - Geske, Grant D. (2008)
A focused library of N-aryl l-homoserine lactones was designed around known lactone leads and evaluated for antagonistic and agonistic activity against quorum-sensing receptors in Agrobacterium tumefaciens, Pseudomonas aeruginosa, and Vibrio fischeri. Several compounds were identified with significantly heightened activities relative to the lead compounds, and new structure-activity relationships (SARs) were delineated. Notably, 4-substituted N-phenoxyacetyl and 3-substituted N-phenylpropionyl l-homoserine lactones were identified as potent antagonists of TraR and LuxR, respectively.